2009
DOI: 10.1002/hbm.20902
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and shared cerebral activations in processing innocuous versus noxious contact heat revealed by functional magnetic resonance imaging

Abstract: Whether innocuous heat (IH)-exclusive brain regions exist and whether patterns of cerebral responses to IH and noxious heat (NH) stimulations are similar remain elusive. We hypothesized that distinct and shared cerebral networks were evoked by each type of stimulus. Twelve normal subjects participated in a functional MRI study with rapidly ramped IH (38 degrees C) and NH (44 degrees C) applied to the foot. Group activation maps demonstrated three patterns of cerebral activation: (1) IH-responsive only in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 64 publications
7
50
0
Order By: Relevance
“…This pattern of activation is consistent with previous studies (Tracey et al, 2000;Laureys et al, 2002;Tseng et al, 2010). Most regions were activated bilaterally, but showed stronger activation on the side contralateral to the stimulus.…”
Section: Fmri Activation Pattern and Outcomessupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern of activation is consistent with previous studies (Tracey et al, 2000;Laureys et al, 2002;Tseng et al, 2010). Most regions were activated bilaterally, but showed stronger activation on the side contralateral to the stimulus.…”
Section: Fmri Activation Pattern and Outcomessupporting
confidence: 92%
“…The stimulation temperature was kept at 42 ± 2°C and the baseline temperature was 21°C (room temperature). Thermal stimulation was carried out by putting a plastic bag containing warm water to the whole plantar surface of one of the subject's feet for 30 s. This ensured that each subject received abundant stimulation, but would suffer no adverse consequences (Moulton et al, 2005;Tseng et al, 2010).…”
Section: Thermal Stimulation/fmri Protocolmentioning
confidence: 99%
“…Agreeing with the results from previous studies using PET (Casey et al, 1996;Craig et al, 2000), MEG (Maihofner et al, 2002) and fMRI (Davis et al, 1998;Seifert and Maihofner, 2007) we found a significant increased activation in brain areas belonging to the pain neuromatrix during painful stimulation (for review see Apkarian et al (2005) and ). Besides insular activations, the main finding of our factorial analysis results was a main effect of innocuous stimulation with increased activation of the parietal cortex as recently shown for innocuous contact-heat stimulation (Tseng et al, 2010). Regarding the insular cortex a main effect of pain with increased activation during noxious compared to innocuous stimuli was detected in bilateral aINS and contralateral pINS.…”
Section: Discussionmentioning
confidence: 55%
“…76 and controls in Ref. 78). There was no significant difference in age (P 5 0.38, Mann-Whitney U test) or gender (P 5 0.11, Fisher exact test) distribution between the patients and controls.…”
Section: Control Participantsmentioning
confidence: 97%